2018
DOI: 10.1038/s41598-018-29488-2
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Attention Deficit/Hyperactivity Disorder among Chinese Children and Adolescents

Abstract: Updating the worldwide prevalence estimates of attention-deficit hyperactivity disorder (ADHD) has significant applications for the further study of ADHD. However, previous reviews included few samples of Chinese children and adolescents. To conduct a systematic review of ADHD prevalence in Mainland China, Hong Kong, and Taiwan to determine the possible causes of the varied estimates in Chinese samples and to offer a reference for computing the worldwide pooled prevalence. We searched for PubMed, Embase, PsycI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 43 publications
1
43
2
1
Order By: Relevance
“…There is a controversy over the true prevalence of ADHD, the knowledge of which is crucial for allocation of health care resources and identification of research priorities ( 8 ). Several literature reviews have reported a wide range of prevalence estimates throughout the world, varying from 1% to 20% among school-aged children ( 9 - 11 ). Variability across studies can be explained in part by the diagnostic criteria used to define ADHD, source of information, and requirement of impairment for the diagnosis ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a controversy over the true prevalence of ADHD, the knowledge of which is crucial for allocation of health care resources and identification of research priorities ( 8 ). Several literature reviews have reported a wide range of prevalence estimates throughout the world, varying from 1% to 20% among school-aged children ( 9 - 11 ). Variability across studies can be explained in part by the diagnostic criteria used to define ADHD, source of information, and requirement of impairment for the diagnosis ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, numerous studies attempted to determine the prevalence of ADHD. However, prevalence rates for children and adolescents differ significantly among different studies, from as low as nearly 1% to as high as nearly 20% [5]. A systematic review and meta-regression analysis including 102 studies comprising 171,756 subjects from all world regions reported an ADHD/Hyperkinetic Disorder (HD) worldwide-pooled prevalence of 5.29% [6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In Hong Kong (HK), ADHD prevalence is estimated at around 6•4% in children and adolescents. 3 Guidelines for ADHD from North America, the UK, and Europe recommend the use of stimulant medications, such as methylphenidate (MPH) and amphetamines, when pharmacological intervention is considered appropriate for management of ADHD and that MPH is recommended as a first-line therapy in many countries. [4][5][6][7][8] Recent studies have shown the prevalence of ADHD medication is increasing over the past decade, and that MPH is the most commonly prescribed ADHD medication in many countries.…”
Section: Introductionmentioning
confidence: 99%